Analisis Pelaksanaan Aplikasi E-office dan E-dokument di RSUD Siti Fatimah Provinsi Sumatera Selatan - Alhadi, Bahrudin; Saswita, Saswita; Febrianza, Muhammad (@-Publik: Jurnal Administrasi Publik, 2025)
This thesis is entitled “Implementation Analysis ApplicationE-office AndE-dokument At the Siti Fatimah Hospital in South Sumatra Province." This research aims to analyze the implementation of E-office and E-dokument Applications at Siti Fatimah Hospital, South Sumatra Province using qualitative type methods and a case study approach which then produces a summary.: (1) Regarding planning, the results of the research included: (a) implementation of the application E-office and E-dokument already has a clear goal, namely to be able to develop the performance of employees or employees, so that they are able to provide convenience and always accelerate the implementation of performance, one of the efforts as a medium for performance transparency. (b) the nature of the application implementation policy E-office and E-dokument at the Siti Fatimah Hospital in South Sumatra Province in the form of South Sumatra provincial governor regulation Number 41 of 2010 Concerning Guidelines for Filing Management within the South Sumatra Provincial government. (c) Strategy for application implementation E-office and E-dokument to all employees or employees at the Siti Fatimah Hospital in South Sumatra Province. (2) Regarding the organization, the research results obtained included: (a) Siti Fatimah Hospital, South Sumatra carried out application socialization E-office and E-dokument to all employees; (b) some employees or employees have responded well to the application E-office and E-dokument and the officers understand enough about the implementation of the application E-office and E-dokument this, because when the application E-office and E-dokument become the most basic thing in the implementation of performance so that it is easier and faster. (3) For coordination, research results were obtained including: (a) The Siti Fatimah Hospital in South Sumatra province provided facilities and provided socialization of the application E-office and E-dokument; (b) Achievement of the target objectives of the application E-office and E-dokument the executor makes the application E-office and E-dokument become single window as well as in the closest context so that users know the application E-office and E-dokument as accelerating and facilitating the performance of employees.